A Logical-Analytical Inquiry into Language and the Rejection of Metaphysics from the Perspective of Rudolf Carnap. (Raparin Journal of Humanities (RJH), 2026)
This study employs an analytical approach. Beginning from the logical analysis of language, it aims to reject metaphysics through the lens of Rudolf Carnap's philosophical position. Logic is considered a gateway to philosophy. It serves as a tool to prevent reasoning from falling into error, and at the same time, to produce precise and meaningful expressions. From the tradition of analytic philosophy—starting with Russell, Frege, and Wittgenstein, and continuing with logical empiricists and logical positivists—logic has undergone a significant transformation. Classical logic was replaced with modern logic, which is fundamentally grounded in mathematics. Mathematics, as a basis for constructing logical foundations and logical expressions, plays a prominent role. Mathematical foundations are considered doubtless and absolutely true (abstract and necessary), which is why analytic philosophers sought to derive reliable knowledge from it, and through it, protect themselves from metaphysical and meaningless terms. That’s why analytic philosophers attempted to systematize logic in a way that aligns with the scientific foundations of their era, and to use it as a scientific method by which scientific terms and concepts could be defined. From the perspective of analytic philosophy, anything that cannot be traced back to empirical foundations or cannot be verified by reliable evidence is considered meaningless. Many metaphysical and abstract philosophical problems, in Carnap's view, are not genuine problems; rather, they result from the misuse of language. Empirical verification is the criterion for distinguishing between meaningful and meaningless expressions—meaning that every term must have a referent in the world and must be verifiable in order to have meaning. For Carnap, language plays a vital role. Human beings must base their language on logic. Scientific investigation must rely on a rational (meta-language), which treats logic as a foundation for language and knowledge. Through such a logical language, a methodological approach to gaining scientific understanding of the world becomes possible. The world, for Carnap, is of utmost importance because what exists in the world is empirically observable. Hence, logic and language are key to understanding the world in a scientific manner. Which terms are logical and which are meaningless? How can language and logic construct the relationship that allows us to distinguish between true and false, meaningful and meaningless expressions? For Carnap, a meaningful expression is either empirical and can be verified or has a basis in logical-analytical structure. Any other expression is considered meaningless and devoid of content.